2010
DOI: 10.1099/vir.0.022020-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the porcine peripheral blood mononuclear cell proteome induced by infection with highly virulent classical swine fever virus

Abstract: Leukopenia and immunosuppression are characteristic clinical manifestations of classical swine fever and peripheral blood mononuclear cells (PBMCs) are major targets of classical swine fever virus. To investigate proteomic expression changes in swine PBMCs during lethal CSFV infection, proteins of PBMCs from five lethally CSFV-infected pigs were resolved by two-dimensional electrophoresis followed by mass spectrometry. Quantitative intensity analysis revealed that 66 protein spots showed altered expression, 44… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 46 publications
0
10
0
1
Order By: Relevance
“…PRDX1 participates in the apoptosis signal-regulating kinase 1 (ASK1)mediated signaling pathway, and plays an inhibitory role in ASK1-induced apoptosis [44]. Its abundance was shown to be decreased in peripheral blood mononuclear cell (PBMC) following CSFV infection in vivo [45]. In our study, the abundance of HSPB1 and PRDX1 were shown to be decreased after IBV infection in ovo by 2-DE and real-time RT-PCR methods.…”
Section: Mock-infected Kidney Ibv-infected Kidneymentioning
confidence: 61%
“…PRDX1 participates in the apoptosis signal-regulating kinase 1 (ASK1)mediated signaling pathway, and plays an inhibitory role in ASK1-induced apoptosis [44]. Its abundance was shown to be decreased in peripheral blood mononuclear cell (PBMC) following CSFV infection in vivo [45]. In our study, the abundance of HSPB1 and PRDX1 were shown to be decreased after IBV infection in ovo by 2-DE and real-time RT-PCR methods.…”
Section: Mock-infected Kidney Ibv-infected Kidneymentioning
confidence: 61%
“…Further, serum metabolite profiles of CSFV-infected piglets clearly demonstrate that the perturbation of host metabolites or metabolic pathways is associated with microbial metabolism, especially the composition and function of gut microbiota. In previous proteomics studies regarding CSFV Shimen infection, only metabolic enzymes involved in glycolysis and TCA cycle, including glyceraldehyde 3-phosphate dehydrogenase (GAPDH), phosphoglycerate mutase (PGAM1), and malate dehydrogenase, were found to be differentially expressed among altered proteins (Sun et al, 2008, 2010). Therefore, this study provided more information about alteration of metabolites and associated pathways in piglets following CSFV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Systems biology with high throughput techniques provides a powerful tool to reveal global changes in gene expression and metabolism associated with disease progression. Alterations in genomic expression profiles and the host proteome after CSFV infection have been determined using transcriptomics and proteomics in studies focused on elucidating alterations in upstream transcripts and proteins in virus-infected leukocytes, mononucleocytes, and PK-16 cells (Sun et al, 2008, 2010; Shi et al, 2009). However, global changes of small molecule metabolites in CSFV-infected piglets have not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that cytokines released from monocytes/macrophages activated by CSFV infection may play a critical role in the induction of immune cell apoptosis [6][7][8], and that proinflammatory and procoagulant cytokines of vascular endothelial cells induced by the virus may disrupt the hemostatic balance and lead to the coagulation and thrombosis seen in acute disease [9]. Proteomic analysis of PK-15 cells in vitro and peripheral blood monuclear cells (PBMC) in vivo following lethal CSFV infection revealed host cell responses to CSFV infection and changes in protein expression associated with CSFV pathogenesis [10,11].…”
Section: Introductionmentioning
confidence: 99%